Analisis Implementasi Model Pengembangan Kurikulum D.K. Wheeler Pada Pembelajaran Bahasa Arab Di Madrasah Tsanawiyah - Fitria, Faiza; Sabila, Anis Nurma; Hilmi, Danial (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Looking at the reality that is happening in the world of education today, the curriculum aspect plays an important role as the main controller of the learning process in all components of educational institutions. This causes the need to hold curriculum development based on the situation and needs of the community around the institution, including the Arabic language curriculum which has been developed several times since its initial formulation by the government. In developing a curriculum, a developer needs to pay attention to curriculum components by referring to a curriculum development model including D.K. Wheeler’s model so that learning objectives can be achieved. This study aims to analyze the implementation of D.K. Wheeler’s curriculum development model at Madrasah Tsanawiyah (MTs) Almaarif 01 Singosari, especially in Arabic subjects which are considered as one of the important materials in learning Islamic schools or madrasah. This research is a descriptive qualitative research based on a literature study by analyzing data from observations, interviews, and document studies. The results showed that the Arabic learning curriculum development model implemented by MTs Almaarif 01 Singosari adopted the D.K. Wheeler in all its aspects including 1) determination of aims and objectives from suitability of the development of Kompetensi Dasar with the development of Kompetensi Inti; 2) determining the learning experience in the form of observing, imitating, listening, and paying attention to content; 3) determination of material in the form of linguistic material development that can be used for joint discussions; 4) organization of learning experiences and materials in the form of mapping in the syllabus; and 5) evaluation in the form of an assessment on the aspects of attitudes, knowledge, and skills.